2017
DOI: 10.1016/j.envpol.2017.04.050
|View full text |Cite
|
Sign up to set email alerts
|

High levels of maternally transferred mercury disrupt magnetic responses of snapping turtle hatchlings (Chelydra serpentina)

Abstract: a b s t r a c tThe Earth's magnetic field is involved in spatial behaviours ranging from long-distance migration to nongoal directed behaviours, such as spontaneous magnetic alignment (SMA). Mercury is a harmful pollutant most often generated from anthropogenic sources that can bio-accumulate in animal tissue over a lifetime. We compared SMA of hatchling snapping turtles from mothers captured at reference (i.e., low mercury) and mercury contaminated sites. Reference turtles showed radio frequency-dependent SMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…The health effects of mercury (Hg) exposure represent a significant threat to ecosystems and human welfare worldwide (Driscoll et al 2013 ), but understanding the risks associated with Hg exposure is complicated by this element’s varied environmental fate and the overarching influences of environmental, biological, and socioeconomic drivers. In its various forms, Hg causes immunotoxicity (Hawley et al 2009 ; Lewis et al 2013 ; Hui et al 2016 ; Zhang et al 2016 ; Crowe et al 2017 ) and nephrotoxicity (Tchounwou et al 2003 ), diminishes neurological capacity and neurobehavioral function (Steuerwald et al 2000 ; Basu et al 2005 ; Clarkson and Magos 2006 ; Mergler et al 2007 ; Scheuhammer and Sandheinrich 2008 ; Depew et al 2012a ; Bridges et al 2016 ; Landler et al 2017 ), alters functioning of three major endocrine axes (Wada et al 2009 ; Meyer et al 2014 ), and impairs reproduction and alters offspring quality (Klaper et al 2006 ; Burgess and Meyer 2008 ; Bergeron et al 2011 ; Hopkins et al 2013 ; Tartu et al 2013 ; Thompson et al in press). The numerous adverse health effects of Hg, coupled with the diverse environmental sources, propensity for long-range transport, complex biogeochemical cycling, and various exposure pathways through food webs and from industrial activities present significant challenges to characterizing and managing the risk of Hg exposure to ecological and public health.…”
Section: Introductionmentioning
confidence: 99%
“…The health effects of mercury (Hg) exposure represent a significant threat to ecosystems and human welfare worldwide (Driscoll et al 2013 ), but understanding the risks associated with Hg exposure is complicated by this element’s varied environmental fate and the overarching influences of environmental, biological, and socioeconomic drivers. In its various forms, Hg causes immunotoxicity (Hawley et al 2009 ; Lewis et al 2013 ; Hui et al 2016 ; Zhang et al 2016 ; Crowe et al 2017 ) and nephrotoxicity (Tchounwou et al 2003 ), diminishes neurological capacity and neurobehavioral function (Steuerwald et al 2000 ; Basu et al 2005 ; Clarkson and Magos 2006 ; Mergler et al 2007 ; Scheuhammer and Sandheinrich 2008 ; Depew et al 2012a ; Bridges et al 2016 ; Landler et al 2017 ), alters functioning of three major endocrine axes (Wada et al 2009 ; Meyer et al 2014 ), and impairs reproduction and alters offspring quality (Klaper et al 2006 ; Burgess and Meyer 2008 ; Bergeron et al 2011 ; Hopkins et al 2013 ; Tartu et al 2013 ; Thompson et al in press). The numerous adverse health effects of Hg, coupled with the diverse environmental sources, propensity for long-range transport, complex biogeochemical cycling, and various exposure pathways through food webs and from industrial activities present significant challenges to characterizing and managing the risk of Hg exposure to ecological and public health.…”
Section: Introductionmentioning
confidence: 99%
“…Research on orientation in hatchling snapping and Blanding's turtles ( Emydoidea blandingii ) revealed that crop canopies (corn and soy) in agricultural fields impair hatchlings’ ability to use environmental cues for successful dispersal from nests (Pappas, Congdon, Brecke, & Freedberg, ). The damaging effects of mercury on magnetic orientation in hatchling snapping turtles (Landler et al., , Landler, Painter, Youmans, Hopkins, & Phillips, ) highlight the potential for mercury and agriculture to have stronger deleterious effects in combination than in isolation. Taken together, our work and others’ suggest that the impacts of agriculture and pollution on orientation and dispersal performance in hatchling turtles merit further examination.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were brought to the indoor testing set-up and were individually placed into separate radially symmetrical individual chambers (Fig. S3), which have been successfully used in previously published magnetic alignment studies 29,30 . The animals were transported in an opaque black container (13 cm by 13 cm) with a black opaque lid to prevent access to any visual cues while transporting the animal.…”
Section: Methodsmentioning
confidence: 99%